Deterioration of vitamin C in pulp camu-camu ( Myciaria dubia ) stored pasteurized in function of time and storage temperature - Terry Calderón,, Víctor Manuel (2015)
Determines deterioration of vitamin C, present in the pulp of camu camu, a performance was found was 34,31%, (pulp/fruit), with an average content of vitamin C of 1500,1 mg/100 g, pH: 2.8 and 6.3 ° Brix. According to indicators of maturity in the fruit, was obtained the following qualifier, State of maturity pinto ripe, with a color of shell where predominantly red, the appearance of translucent colorless mesocarp and flavor acid.The study determined the deterioration of the pulp of camu camu packaging and pasteurized, taking as an indicator of impairment to vitamin C, depending on the time and temperature. The method of accelerated tests, in order to accelerate the deterioration of vitaminC.The data obtained were analyzed by the method of least squares and whereas the equations chemical kinetics that the order of the reaction was determined first-order (n = 1), then applied the Nicolás Arrhenius equation which correlates the speed of deterioration depending on temperature, establishing the mathematical modelthat simulates the deterioration of vitamin C in the pulp of camu camu stabilized by heat treatment which allows to predict the loss between the temperatures of 20 ° C and 50 ° C, whereupon the obtained model is two related variables.independent time (t) and temperature (Ta), where C (is vitamin C, remnants).